TRANFORMASI PEMBELAJARAN AL-QUR’AN di ERA DIGITAL: INTEGRASI METODE BELAJAR MANDIRI dan KOLABORATIF - Fibri Ilma Nur Aini; Fakhriyah Qudsi; Ahmad Yusam Thobroni (STKIP Subang, 2026)
One of the main pillars of Islamic education is learning the Al-Qur'an, which aims to build students' character and spiritual literacy. However, its implementation in the field is often hindered by monotonous conventional teaching methods, a lack of independent learning, and an inability to adapt to technological advancements, causing Al-Qur'an learning to lag behind other academic disciplines. The purpose of this study is to analyze the importance of optimizing Al-Qur'an learning in the digital era by strategically synergizing independent and collaborative learning methods. The method used is a literature review, examining scientific literature, educational journals, and relevant documents. The collected data were analyzed descriptively and then concluded. The results show that the use of collaborative approaches including participatory activities, peer tutoring, and discussions helps students become more motivated, improves their retention in learning the Al-Qur'an, and reduces boredom. Furthermore, digital transformation enables a more dynamic learning ecosystem. By using digital media such as interactive Al-Qur'an applications, tutorial videos, and online communication platforms, students can explore independently without being limited by space and time. This study finds that the synergy between technological independence and collaborative social interaction not only improves learning outcomes but also enhances teachers' performance as facilitators and learning designers in the internet era.